Pengaruh Kesadaran Kesehatan dan Kepedulian Lingkungan Terhadap Niat Pembelian Telur Ayam Organik - Ismawati Ismawati; Harmini Harmini; Suprehatin Suprehatin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
The current patterns of unsustainable food production and consumption, including conventional agricultural practices, pose significant risks to both human health and environmental sustainability. As a more sustainable alternative, organic eggs are perceived as healthier, safer, of higher quality, and more environmentally responsible. In Indonesia, organic eggs are among the most favored sources of organic protein, reflecting a growing consumer interest. This highlights the importance of understanding the underlying factors that influence consumer decisions to purchase organic eggs. Such insights are essential for producers to develop more effective marketing and communication strategies. Furthermore, purchase intention has been identified as a key predictor of actual consumer behavior. This study aimed to examine the impact of health awareness and environmental concern on the intention to purchase organic eggs, using data from 250 respondents in Bogor City obtained through purposive sampling. Data collection was conducted both online and offline, and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings revealed that health awareness and environmental concern influence purchase intention indirectly through attitudes toward the behavior and perceived behavioral control. Strengthening positive attitudes and perceptions of ease regarding organic eggs is therefore crucial to increasing purchase intention.